A cross-sectional study to investigate motivation for physical activity in a sample of Iranian community-dwelling older adults - Seyed Alireza Derakhshanrad; Emily Piven; Bahareh Zeynalzadeh Ghoochani (Tabriz University of Medical Sciences, 2020)
Background: On the basis of the Social-Ecological Model, there are assumed to be three sources of motivation - intrapersonal, interpersonal, and community motivation - that prompt older adults to participate in physical activity (PA). These three motivational sources can lead to PA behavior adherence. Little empirical research exists that investigates which motivational source is more influential in older adults' adherence to PA, thus creating an area of interest for this research. Methods: A cross-sectional study was used to investigate the relationship between levels of PA and different sources of motivation. The convenience sample of 140 community-dwelling older adults, aged 60 and greater, living in Shiraz, Iran agreed to complete self-reported questionnaires,to measure motivation and PA. Five statistical tests were used: Independent-samples t test, one way ANOVA, Pearson correlation coefficient, chi-square, and ordinal regression. Results: Ordinal regression indicated that gender (P = 0.001, CI: 0.523-2.115) and intrapersonal motivation (P < 0.001, CI: 0.038-0.126) were useful predictors of variations in the levels of PA. Compared to males, females engaged in PA with less frequency (P = 0.006). Community motivation decreased with age (r = - 0.213, P < 0.05). There were no significant relationships between age, educational level, health status, and PA (P > 0.05). Conclusion: Interpersonal and community motivation were insignificant factors for PA participation, perhaps due to non-facilitating environment. Future research should be conducted to investigate the environmental issues that hinder PA participation in older adults.